Genetic monitoring of breeding colony through evaluation of genetic diversity within and between the inbred lines by using microsatellite markers (Journal of Laboratory Animal Science, 2022)
BALB/c strain is the most commonly used animal research mouse model in biology/Bio-medical research. From BALB/c  strain many of inbred, congenic and transgenic models were established and being used for the betterment of humans as  well as domestic animals. At CSIR-IIIM, Jammu animal house facility conducted study for evaluation genetic diversity of  inbred lines of BALB/c strain. Animals were maintained in SPF condition with routine health monitoring. Selection was  conducted based on growth and reproduction performance of the mothers. Four selected lines and an unselected control  line were maintained throughout the experiment. After, 20th generation of full sib mating, we obtained three different lines.  All the three lines of BALB/c strain shows standardized litter size of 8 pups at birth. All line mice were genotyped by using  established 14 pair of microsatellite markers and genetic diversity analysis. The Effective number of alleles was reported  1.021±0.016 in overall experimental population. Shannon’s Index for within lines was 0 and among lines was 0.019±0.014.  The Estimated Diversity (u) was 0 for within lines, 0.052 ±0.036 for control lines and 0.013±0.009 for among population.  Polymorphic information content (PIC) observed in D11Mit260 marker. Line1 was showing very little Genetic distance  with Line 2 (0.154) followed by control line (0.114) and Line 3 (0.074). Control line and Line 2 showed very close genetic  distance (0.010). It is concluded that BALB/c strain has no diversity within line and has very little diversity between lines  after 20th generation of full-sib mating.
Keywords: Mouse; Litter Size; Genetic Diversity; Microsatellite Marker